Utilização da microscopia confocal in vivo no diagnóstico de ceratites micóticas e por Acanthamoeba, na observação do dano e no processo de regeneração neuronal em ceratites infecciosas - Muller, Rodrigo Thiesen [UNIFESP] (2021)
Purpose: (1) and (2) to determine the factors that influence the accuracy of in vivo confocal microscopy (IVCM) for diagnosing infectious keratitis (IK) caused by Acanthamoeba and fungi; (3) to evaluate long-term alterations of corneal innervation in patients with herpes simplex virus (HSV) keratitis using IVCM; (4) to investigate the alterations of corneal nerves in patients with IK using IVCM; and (5) to report long-term alterations of corneal nerves in patients with bacterial IK using IVCM. Methods: (1) the first study analyzed 27 patients with Acanthamoeba IK and 34 patients with bacterial IK. Sensitivity and specificity of IVCM for diagnosing Acanthamoeba IK were investigated; (2) the second study included 21 patients with fungal IK and 24 patients with bacterial IK. IVCM images were evaluated for the presence of fungal filamentous; (3) the third study included 16 patients with history of HSV keratitis and 15 agematched normal controls. IVCM images were performed at two time-points: baseline and then after a mean follow-up of 37.3 ± 1.7 months; (4) the fourth study recruited 56 patients with IK as well as 30 normal healthy controls. Corneal sensation and IVCM images were obtained prospectively; and (5) in the fifth study, 13 patients with unilateral bacterial keratitis and 12 controls were enrolled in the study. IVCM was performed in all patients at two-time points: acute phase of the infectious keratitis and after 28 ± 0.6 months from resolution of the infection. Results: In relation to (1) and (2), IVCM had average sensitivity and specificity for Acanthamoeba IK diagnosis of 69% ± 2% and 97% ± 4% for experienced observers, and 59% ± 7% and 92% ± 10% for inexperienced observers, respectively, and sensitivity and specificity for fungal filamentous detection of 71% ± 0% and 89% ± 3% for experienced observers, and 42% ± 6% and 87% ± 17% for inexperienced observers; (3) in the third study, corneal nerve density was significantly decreased in both affected and contralateral unaffected eyes with IK by HSV. There was an increase on nerve density in the affected eyes with HSV overtime; (4) in the fourth study, corneal nerves were significantly reduced during the acute phase in eyes with IK. Despite significant regeneration overtime, the nerve density was still significantly reduced compared to controls; (5) in the fifth study, corneal nerve density was significantly reduced in patients with bacterial keratitis compared to controls. There was partial regeneration of the corneal nerves over the 28-month follow-up. Conclusion: IVCM reveals high sensitivity and moderate specificity on identification of Acanthamoeba cysts and filamentous fungal. There is modest corneal nerve regeneration overtime in patients with HSV keratitis. Patients with IK show profound corneal nerve diminishment during the acute phase of the infection. Despite significantly regeneration of nerves overtime, the subbasal nerve density sustain altered even after more than 2 years after cornea infection resolution.